2016
DOI: 10.3389/fnmol.2016.00071
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Biomarkers for Monitoring Brain Pathophysiology in FMR1 Premutation Carriers

Abstract: Premutation carriers have a 55–200 CGG expansion in the fragile X mental retardation 1 (FMR1) gene. Currently, 1.5 million individuals are affected in the United States, and carriers are at risk of developing the late-onset neurodegenerative disorder Fragile X-associated tremor ataxia syndrome (FXTAS). Limited efforts have been made to develop new methods for improved early patient monitoring, treatment response, and disease progression. To this end, plasma metabolomic phenotyping was obtained for 23 premutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 103 publications
6
34
0
Order By: Relevance
“…Conversely, decreased glucuronidation of xenobiotics such as bisphenol A has been observed in patients with Parkinson's Disease (Landolfi et al, 2017). Finally, metabolic profiling of FMR1 premutation carriers who have intermediate (55-200 copies) CGG repeat expansion but nevertheless manifest FMRP deficiency, showed elevated levels of glucuronic acid (Giulivi et al, 2016). We found FX-specific DSBs in genes coding for the most important enzymes in phase I (cytochrome P450 enzymes, specifically CYP2C9 and CYP2C19) and phase II (UGTs, specifically the UGT1A subfamily isoforms) xenobiotics metabolic pathways.…”
Section: Discussionmentioning
confidence: 79%
“…Conversely, decreased glucuronidation of xenobiotics such as bisphenol A has been observed in patients with Parkinson's Disease (Landolfi et al, 2017). Finally, metabolic profiling of FMR1 premutation carriers who have intermediate (55-200 copies) CGG repeat expansion but nevertheless manifest FMRP deficiency, showed elevated levels of glucuronic acid (Giulivi et al, 2016). We found FX-specific DSBs in genes coding for the most important enzymes in phase I (cytochrome P450 enzymes, specifically CYP2C9 and CYP2C19) and phase II (UGTs, specifically the UGT1A subfamily isoforms) xenobiotics metabolic pathways.…”
Section: Discussionmentioning
confidence: 79%
“…Chronic fatigue is a common symptom of premutation carriers with and without FXTAS and it has a significant effect on their daily lives ( 85 , 86 ). It is likely associated with the mitochondrial dysfunction described previously in premutation carriers; previous studies have linked chronic fatigue in carriers with the severity of mitochondrial dysfunction ( 32 , 33 ).…”
Section: Chronic Fatiguementioning
confidence: 84%
“…The extensive molecular pathology and mitochondrial studies that have been carried out in premutation carriers has led to a wealth of molecular information to link to the psychiatric problems that carriers experience ( 11 , 12 , 32 , 33 ). We know that psychiatric problems (usually depression and/or anxiety) occur before the neurological problems develop in those with FXTAS ( 34 , 35 ).…”
Section: Neuropsychiatric Problemsmentioning
confidence: 99%
“…Consistently, researchers found that the metabotropic glutamate (Glu) receptor 5 and GABA pathways are altered in the brains of FXTAS patients (Pretto et al, 2014). Additionally, lower plasma concentrations of phenylethylamine (PEA) were also found in premutation carriers, which may reflect incipient nigrostriatal degeneration (Giulivi et al, 2016a).…”
Section: Amino Acids Derivatives and Biogenic Aminesmentioning
confidence: 92%
“…Moreover, Giulivi et al (2016a) hypothesized that given the increased levels of the Krebs cycle intermediates (citrate, isocitrate and aconitate), the activity of AKGDH is decreased in premutation carriers, resulting in an increased flux from alphaketoglutarate to glutamate, which subsequently culminates in the elevation of glutamine, GABA, and GHB levels (Figure 1, blue dashed circle). Consistently, researchers found that the metabotropic glutamate (Glu) receptor 5 and GABA pathways are altered in the brains of FXTAS patients (Pretto et al, 2014).…”
Section: Amino Acids Derivatives and Biogenic Aminesmentioning
confidence: 99%